Are They Learning or Playing? Students' Perception Traits and Their Learning Self-Efficacy in a Game-Based Learning Environment. (January 2020) - Lu, Yu-Ling; Lien, Chi-Jui
As game-based learning continues to draw attention, students' perceptions toward classroom activities are vital in influencing the quality of learning. This study used the social cognitive theory to show the perception traits of learning and playing in game-based environments and for students to identify their self-efficacy toward game-based learning by different trait groups. The game Formosa Hope was used in an experiment with 362 fifth- and sixth-grade students at ages 11 to 12 years as participants. Three perception traits were identified through a two-step cluster analysis: I—strong perceptions of learning and playing, II—moderate perceptions of learning and playing, and III—strong perception of playing but weak perception of learning. This study showed that regardless of trait type, students demonstrated positive self-efficacy, with those with Trait I having significantly higher self-efficacy than those with Traits II and III, indicating that students' positive perceptions of learning and playing are essential in prompting self-efficacy in game-based learning.